2020
DOI: 10.1186/s43556-020-00018-9
|View full text |Cite
|
Sign up to set email alerts
|

Low dose of emetine as potential anti-SARS-CoV-2 virus therapy: preclinical in vitro inhibition and in vivo pharmacokinetic evidences

Abstract: The global pandemic of COVID-19 has attracted extensive drug searching interets for the new coronavirus SARS-CoV-2. Although currently several of clinically used “old” drugs have been repurposed to this new disease for the urgent clinical investigation, there is still great demand for more effective therapies for the anti-infections. Here we report the discovery that an “old” drug Emetine could potently inhibit SARS-CoV-2 virus replication and displayed virus entry blocking effect in Vero cells at low dose. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 26 publications
(32 reference statements)
0
34
0
Order By: Relevance
“…Wang et al 123 reported the emetine ( 56 , Fig. 28 ) can significantly influence SARS-CoV-2 entry and replication, meanwhile reducing inflammatory factor level in vitro .…”
Section: Medicinal Chemistry Strategies In Seeking Effective Sars-cov-2 Inhibitorsmentioning
confidence: 99%
“…Wang et al 123 reported the emetine ( 56 , Fig. 28 ) can significantly influence SARS-CoV-2 entry and replication, meanwhile reducing inflammatory factor level in vitro .…”
Section: Medicinal Chemistry Strategies In Seeking Effective Sars-cov-2 Inhibitorsmentioning
confidence: 99%
“…Emetine has anti-malaria and anti-inflammatory properties. Moreover, it has shown antiviral activity against various DNA and RNA viruses such as Zika virus and Ebola virus [14,27,50,108,123]. Previous in vitro studies have demonstrated the inhibitory activity of emetine against MERS-CoV and SARS-CoV [38,101].…”
Section: Emetinementioning
confidence: 99%
“…Emetine, which has displayed inhibitory effects on Zika virus and Ebola virus (Yang et al, 2018), has been reported to reduce SARS-CoV-2 replication in a number of in vitro studies (Choy et al, 2020;Wang et al, 2020b;Jan et al, 2021;Kumar et al, 2021). A small observational study has also shown that, while emetine did not accelerate viral clearance, emetine appeared to improve blood oxygen concentrations and breathing difficulties among symptomatic COVID-19 patients (Fan et al, 2021).…”
Section: Alkaloidsmentioning
confidence: 99%